Monotone and Concave Positive Solutions to a Boundary Value Problem for Higher-Order Fractional Differential Equation - Jinhua Wang; Hongjun Xiang; Yuling Zhao (Abstract and Applied Analysis)
We consider boundary value problem for nonlinear fractional differential equation D0+αu(t)+f(t,u(t))=0,  0<t<1,  n-1<α≤n,  n>3,  u(0)=u'(1)=u′′(0)=⋯=u(n-1)(0)=0, where D0+α denotes the Caputo fractional derivative. By using fixed point theorem, we obtain some new results for the existence and multiplicity of solutions to a higher-order fractional boundary value problem. The interesting point lies in the fact that the solutions here are positive, monotone, and concave.